The Simple View, Instructional Level, and the Plight of Struggling Fifth-/Sixth-Grade Readers. Issue 3 (4th May 2017) - Morris, Darrell; Meyer, Carla; Trathen, Woodrow; McGee, Jennifer; Vines, Nora; Stewart, Trevor; Gill, Tom; Schlagal, Robert
ABSTRACT: This study explored print-processing and vocabulary differences among a group of 5th- and 6th-grade students who had scored below the 50th percentile on a standardized reading test. Guided by the simple view of reading, we applied cut scores (low/high) to the students' performance on print-processing and vocabulary tasks. The design allowed for the placement of students in 1 of 4 reader profiles: (a) high print processing/low vocabulary (25%), (b) high print processing/high vocabulary (14%), (c) low print processing/high vocabulary (14%), or (d) low print processing/low vocabulary (48%). An important finding was that 62% of the students could not read grade-level text with adequate accuracy and rate. In fact, many could not read comfortably a full level below their grade placement. We consider instructional implications.